Perbandingan Metode Eksperimen Sederhana dan Simulasi Phet Listrik Terhadap Sikap Ilmiah Siswa di Pembelajaran Fisika - Muhammad Afrialdi, Raden; Rohima Rohima (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2025)
This study aims to compare the effectiveness of simple experimental methods and static electricity PhET simulations in developing scientific attitudes and improving learning outcomes for grade XII students. Grade XII PMIA 1 was taught using simple experiments utilizing readily available tools, while grade XII PMIA 2 used Static Electricity PhET simulations to visualize concepts interactively. This study used a quasi-experimental design with a nonequivalent control group design through the administration of pretests and posttests to both classes. The results showed that both methods provided significant improvements in understanding the concept of static electricity. The simple experimental method produced large improvements but with a more varied distribution of scores, while the PhET simulation produced a higher average post-test score and a more even increase among students. These findings indicate that PhET simulations are more effective in providing stability in understanding abstract material, while simple experiments remain superior in providing concrete experiences to students. Overall, both methods can be used as effective learning alternatives in improving students' learning outcomes and scientific attitudes in static electricity.